2021
DOI: 10.3390/biom11060803
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Key Effector of Necroptotic Cell Death, MLKL, in Mouse Models of Disease

Abstract: Necroptosis is an inflammatory form of lytic programmed cell death that is thought to have evolved to defend against pathogens. Genetic deletion of the terminal effector protein—MLKL—shows no overt phenotype in the C57BL/6 mouse strain under conventional laboratory housing conditions. Small molecules that inhibit necroptosis by targeting the kinase activity of RIPK1, one of the main upstream conduits to MLKL activation, have shown promise in several murine models of non-infectious disease and in phase II human… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 98 publications
1
10
0
Order By: Relevance
“…They were however shown to occur in trans at 10–12 times the expected frequency in a cohort of patients suffering from chronic recurrent multifocal osteomyelitis (CRMO) [ 27 ]. While this association has not been independently replicated in a second CRMO patient cohort to date, this finding does fit nicely with mouse and human studies that implicate ‘unchecked’ necroptosis in the progression of inflammatory diseases [ 20 , 26 ].…”
Section: Common Mlkl Missense Variants In Inflamma...supporting
confidence: 73%
See 3 more Smart Citations
“…They were however shown to occur in trans at 10–12 times the expected frequency in a cohort of patients suffering from chronic recurrent multifocal osteomyelitis (CRMO) [ 27 ]. While this association has not been independently replicated in a second CRMO patient cohort to date, this finding does fit nicely with mouse and human studies that implicate ‘unchecked’ necroptosis in the progression of inflammatory diseases [ 20 , 26 ].…”
Section: Common Mlkl Missense Variants In Inflamma...supporting
confidence: 73%
“…When considering the pathophysiological impacts of necroptosis, we must not only consider genetic variation in MLKL itself , but also variation in genes that can inappropriately unleash, amplify, or even dampen the cellular activity of MLKL. Based on observations of important MLKL regulatory genes gleaned from genetically modified mice [ 20 ], we have plotted for the purposes of this review the number of disease associated human mutations reported in ClinVar [ 52 ], as accessed in September 2021 ( Figure 2A ). This tally is strongly dominated by RIPK1 , TNFAIP3 (encoding A20) and CASP8 , where several unique LOF or missense mutations are characterised by autoinflammatory and lymphoproliferative syndromes [ 53 ].…”
Section: Disease Causing Gene Variants Identified In Important Upstre...mentioning
confidence: 99%
See 2 more Smart Citations
“…In mammals, necroptosis appears to have evolved in conjunction with microbial pathogens, as there is evidence for a variety of bacterial and viral proteins that target the necroptosis pathway [ 1 5 ]. There is also increasing evidence implicating necroptosis in a range of inflammatory, autoimmune and neurodegenerative diseases (reviewed in [ 6 , 7 ]) and cancers (reviewed in [ 8 ]). For these reasons, there has been much interest in the cell death community in developing inhibitors of necroptosis.…”
Section: Introductionmentioning
confidence: 99%